Monolith-to-Microservices Migration in Enterprise Operations Platforms: A Workflow-Oriented Architecture (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2024)
Monolith-to-microservices migration is widely practiced in enterprise engineering but rarely well characterized in the literature. Engineering teams often treat the migration as a refactoring exercise, when in reality it is a workflow re-architecting exercise, and the difference determines whether the migration improves or harms the operations platform. This article develops a workflow-oriented treatment of monolith-to-microservices migration in enterprise operations platforms. We position the migration as a workflow decomposition problem rather than a code decomposition problem; we identify the five workflow archetypes that dominate enterprise operations platforms (long-running approvals, batch orchestration, event-driven state transitions, human-in-the-loop review, and time-sensitive material flows), and show how each archetype maps to a distinct decomposition pattern: strangler-fig with bounded context for long-running approvals, saga orchestration for business-process flows, event-carried state transfer for cross-domain propagation, dual-write bridging for human-in-the-loop review, and shadow-write reconciliation for time-sensitive material flows. We then examine the migration mechanics that determine whether the re-architecting succeeds in production: workflow-aware dependency analysis, contract-first API design, idempotent compensation, gradual traffic shifting with feature-flagged routing, and observability that surfaces in-flight workflow state. We close with a phased migration framework that connects migration decisions to workflow properties rather than to service boundaries drawn prematurely. The result is a practitioner’s map for migrating enterprise operations platforms in a way that preserves correctness during the migration while improving the architecture that the platform leaves behind
Keywords: monolith-to-microservices migration; workflow decomposition; strangler fig pattern; saga orchestration; event-carried state transfer; contract-first API; idempotent compensation; enterprise operations platforms; bounded context